2011
DOI: 10.5336/medsci.2010-20795
|View full text |Cite
|
Sign up to set email alerts
|

Violence Towards Healthcare Workers in Turkey: A Systematic Review

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu ça lış ma Tür ki ye' de sağ lık ça lı şan la rı na yö ne lik şid det le il gi li Ocak 1999-Tem muz 2010 ta rih le ri ara sın da ya yın lan mış ça lış ma la rın göz den ge çi ril me si ve ça lış ma lar dan el de edi len ve ri le rin sis te ma tik bi çim de in ce len me si ama cıy la ger çek leş ti ril miş tir. G Ge e r re eç ç v ve e Y Yö ön n t te em m l le er r: : Konuy la il gi li 41 ulu sal ve ulus la ra ra sı ya yı na ula şıl mış olup araş tır ma ya da hil edil me kri ter le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 27 publications
0
8
1
4
Order By: Relevance
“…When the report status following violence was examined generally, it was observed that most healthcare workers did not report violence (10,18). The finding that only one-third of violent incidents in our clinic were reported, might have arisen from the avoidance of healthcare workers from legal procedures, the thought that they could not spare time for legal procedures in their busy schedule and possibly not getting a result, and considering being attacked as part of the profession.…”
Section: Discussionmentioning
confidence: 91%
“…When the report status following violence was examined generally, it was observed that most healthcare workers did not report violence (10,18). The finding that only one-third of violent incidents in our clinic were reported, might have arisen from the avoidance of healthcare workers from legal procedures, the thought that they could not spare time for legal procedures in their busy schedule and possibly not getting a result, and considering being attacked as part of the profession.…”
Section: Discussionmentioning
confidence: 91%
“…Çalışmamızda şiddetin olası nedenleri arasında her iki cinsiyette de en sık gösterilen neden; uzun süre sırada beklenilmesi ve sağlık sisteminin işleyişindeki aksaklıklara maruz kalınmasıydı. Literatürde de benzer şekilde uzun bekleme süreleri, hasta ve hasta yakınlarının beklentilerinin karşılanmaması, sağlık çalışanlarının zaman kısıtlılığı, uzun çalışma süreleri, ödeme zorlukları, hasta ve/veya yakınları ile sağlık çalışanları arasındaki iletişim sorunları ve kişisel sorunlar şiddet eylemlerinin nedenleri olarak gösterilmektedir [14,15]. Beyaz kod bildirimlerinin analiz edilmesine yönelik yapılan bir çalışma hastaların kanunsuz işlem yapma talebi (%35) karşılanmadığında şiddete başvurduklarını ortaya koymaktadır [16].…”
Section: Discussionunclassified
“…As a result, a situation known commonly as 'burnout syndrome' emerges. 38,39 The burnout syndrome is defined as holding a negative view of current events, frequent despair, and lost productivity and motivation. 40 Reluctance among physicians to work in the ED is one consequence of burnout syndrome.…”
Section: Discussionmentioning
confidence: 99%